Congenital adrenal hyperplasia. Issue 10108 (11th November 2017) - El-Maouche, Diala; Arlt, Wiebke; Merke, Deborah P
Summary: Congenital adrenal hyperplasia is a group of autosomal recessive disorders encompassing enzyme deficiencies in the adrenal steroidogenesis pathway that lead to impaired cortisol biosynthesis. Depending on the type and severity of steroid block, patients can have various alterations in glucocorticoid, mineralocorticoid, and sex steroid production that require hormone replacement therapy. Presentations vary from neonatal salt wasting and atypical genitalia, to adult presentation of hirsutism and irregular menses. Screening of neonates with elevated 17-hydroxyprogesterone concentrations for classic (severe) 21-hydroxylase deficiency, the most common type of congenital adrenal hyperplasia, is in place in many countries, however cosyntropin stimulation testing might be needed to confirm the diagnosis or establish non-classic (milder) subtypes. Challenges in the treatment of congenital adrenal hyperplasia include avoidance of glucocorticoid overtreatment and control of sex hormone imbalances. Long-term complications include abnormal growth and development, adverse effects on bone and the cardiovascular system, and infertility. Novel treatments aim to reduce glucocorticoid exposure, improve excess hormone control, and mimic physiological hormone patterns.